The impact of foreign and independent commissioners on bank performance: empirical evidence from Indonesia - Zakaria, Adam; Mardiyati, Umi; Pena, Cassania Dela (Global Advances in Business Studies, 2022)
The purpose of this study is to empirically prove the influence of foreign commissioners and independent commissioners on bank performance. This research is a quantitative study using secondary data in the form of annual reports issued by companies in the banking sector. The research sample is banking companies in the 2010-2019 period. The results of the study show that foreign commissioners have a significant negative effect on bank performance with ROA and ROE proxies and have a significant positive effect on bank performance with NIM proxies. Meanwhile, independent commissioners have no influence on bank performance using either ROA, ROE, or NIM proxies.